ANALISIS PERILAKU PENGGUNAAN APD TERHADAP KECELAKAAN KERJA PADA PEKERJA PABRIK KELAPA SAWIT : LITERATUR REVIEW - Shabrina Rahmadani; Susilawati (CV. ADIBA AISHA AMIRA, 2022)
Work accident is an event that is clearly unwanted and often unexpected which can cause loss of time, property or loss of life that occurs in an industrial work process or related to it. The role of Occupational Safety and Health (K3) is vital, apart from being an aspect of protecting the workforce it also plays a role in protecting company assets. Personal Protective Equipment is a tool that has the ability to protect someone whose function is to isolate part or all of the body from potential hazards in the workplace. This study aims to analyze the behavior of using PPE towards work accidents in palm oil factory workers. This research is a research in the form of Literature Review. The results of the literature review on the findings of the first article are that there are 2 factors that have a significant relationship, namely knowledge (p=0.023) and attitude (p=0.019). The findings in the second article are factors related to the incidence of work accidents in workers are knowledge, action and work environment factors while attitudes and compliance with procedures are not factors related to the occurrence of work accidents in workers in the production section of the palm oil factory. The findings in the third article are there is a relationship between the use of PPE with work accidents in coconut workers with a p value of 0.020. The findings in the fourth article are that almost all 63 workers (92.07%) workers do not use Personal Protective Equipment incompletely and out of 63 workers almost all (90.48%) workers do not often experience work accidents. The findings in the fifth article are that workers who do not fully use PPE are 3.9 times more at risk of experiencing work accidents compared to workers who use PPE completely